2012
DOI: 10.1111/j.1464-410x.2012.11274.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral obesity is a strong predictor of perioperative outcome in patients undergoing laparoscopic radical nephrectomy

Abstract: What ' s known on the subject? and What does the study add? Obesity is a common and growing problem in industrialized countries, and metabolic syndrome has been the focus of much attention recently, particularly with respect to obesity. Obesity is thought to be a major factor infl uencing surgical complexity during abdominal surgery, including laparoscopic surgery.In this study, we focused on visceral obesity which has been recognized as the most important pathogenic factor in metabolic syndrome. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 49 publications
4
50
0
1
Order By: Relevance
“…Although we have not yet applied these cutoff points to an external data set for validation, we plan to do that in the near future to verify the conclusions. Our findings in this ventral hernia study population are in line with prior findings published in the colorectal and urology literature, which found that wound and total complications are increased with increasing AWT [5,7,8]. Patients with large ventral hernias (classified as hernia area >100 cm 2 ) are at increased risk of seroma formation and worse long-term quality of life outcomes according to recently published data [12].…”
Section: Discussionsupporting
confidence: 94%
“…Although we have not yet applied these cutoff points to an external data set for validation, we plan to do that in the near future to verify the conclusions. Our findings in this ventral hernia study population are in line with prior findings published in the colorectal and urology literature, which found that wound and total complications are increased with increasing AWT [5,7,8]. Patients with large ventral hernias (classified as hernia area >100 cm 2 ) are at increased risk of seroma formation and worse long-term quality of life outcomes according to recently published data [12].…”
Section: Discussionsupporting
confidence: 94%
“…In the past, the impact of visceral fat area on surgical outcome were well elucidated [24, 25], and some studies indicated that the larger visceral or peri-organ fat areas prolonged the operative time of laparoscopic radical nephrectomy [26], laparoscopic adrenalectomy [27], and laparoscopic radical prostatectomy [28]. In the present study, we measured the retroperitoneal fat tissue thickness using preoperative standard 2-dimensional transverse CT scan images.…”
Section: Discussionmentioning
confidence: 99%
“…High BMI has been correlated with adverse surgical outcomes in several fields including urological, hepatobiliary and gastrointestinal surgery [6,7,16,17]. Studies on CD such as Causey's study of 2,319 CD patients undergoing abdominal operations have also associated obesity with increased morbidity [10].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological state of being overweight or obese has been suggested to be a low-grade inflammatory state. Obesity has been associated with the development of various autoimmune diseases [2,3], a more severe phenotype in IBD [4] and increased postoperative surgical complications after colorectal [5] and other surgery [6,7]. …”
Section: Introductionmentioning
confidence: 99%